Estudo do ilhamento não intencional em microrredes baseadas em conversores eletrônicos de potência - Ioris, Darlan (2021)
The current development of electric energy sources is mainly based on the use of distributed energy resources (DERs), which include distributed generation (DG) and energy storage systems. Microgrids (MGs) are an attractive alternative to overcome the challenges in integrating DERs into the traditional electrical system and to ensure reliability and optimal use of energy resources. MGs can operate islanded or connected to the main electrical system. The transition from connected to islanded mode, called islanding, can present several challenges for the MG, especially when islanding happens unintentionally. The present work uses simulations in the Matlab/Simulink environment to study the dynamic performance of a MG based on electronic power converters (EPC) in the event of unintentional islanding of the MG caused by the main grid shutdown. Regarding existing studies in the literature, two situations in unintentional islanding that have not yet been the subject of extensive investigation are addressed: the existence of a period of time in the detection of MG islanding that leads to a time delay in the execution of the necessary control actions for the islanded operation and the existence of loads external to the MG that can influence the transient of the MG islanding. We studied different electrical models of DERs that make up the MG and that can be used in simulations, varying in the representation of the EPC (switched or by average-value) and in the representation of the energy source (ideal DC source or primary source model), resulting in a description of DER modeling. The models are used to simulate MG islanding with different time delays and with two different operating and control strategies for battery-powered DERs: changing the operating mode (from grid-feeding to grid-supporting) and without changing the operating mode (continuously in grid-supporting). In simulations with different DER models, it appears that the model with the primary source represented and the EPC modeled by average-value has lower computational cost and adequate dynamic representation for this study. The simulations with different time delays show that the strategy changing the operating mode has considerable voltage and frequency deviations after islanding due to the temporary lack of control, while the strategy without changing the operating mode has a better dynamic result. However, it can lead to the occurrence of overload in DERs due to the external load.